Articulating Islamist sectarian group antagonism memes on the Indonesian politics - Adi Bayu Mahadian,; Rohani Hashim,; Hasrina Mustafa, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Polarisation among Indonesians has arisen after the presidential rematch in the 2019 presidential election. It stimulated the repressive action of the Jokowi government has made Indonesian democracy to be on decline. Some scholars consider this as an atavism of an entrenching ideological conflict since hundreds of years ago between nationalism vs. Islamism. However, we argue that polarisation is more complex than what we expected before. This article examines the Islamist grassroots discourses to get an alternative perspective regarding the resurrection of conservatism in Indonesia. We collected and analysed qualitatively data of internet memes during the 2019 Indonesia Presidential campaign. We argue that antagonism occurred among the Islamist sectarian groups as a continuation of the Aksi Bela Islam (The Defending Islam Movement) in 2016. The antagonism among the groups indicates the rise of the Islamic radical-conservatism groups through the presentation of the antagonism between Islam Nusantara and Islamist puristic movement. The Islamic radical-conservatism group has successfully exploited the anti-Ahok movement with the Bela Islam (defending Islam) discourse. However, using Islamist issues during the 2019 presidential election has represented the triumph of the Politics of Islam: Islamization of Indonesian political ideology. Islam has harmonised into nationalism and secularism despite the internet memes' incoherent and irrational language. The triumph of Islamic hegemony transformed and infected Indonesia's political ideology. Islam has become an obligatory symbol in Indonesian politics.